Permasalahan Narkoba di Indonesia dan Ancaman Bonus Demografi - Supratman, Dindin; Runturambi, Arthur Josias Simon (Jurnal Kajian Stratejik Ketahanan Nasional, 2022)
The demographic bonus is a phenomenon where the population structure is very beneficial in terms of development because the population of productive age is very large, while the proportion of young people is getting smaller and the proportion of old people is not much. Indonesia will get a demographic bonus, which is the number of labor force ages (15-64 years) reaching around 70 percent, while 30 percent of the population is not productive (aged 14 years and under and aged over 65 years) which will occur in 2020-2030 . On the one hand, demographic bonuses benefit because of the abundance of productive Human Resources (HR). But on the other hand, disaster is ready to lurk if the abundant workforce is not of good quality. Productive age population who are not in their best performance will certainly be excluded. Unpreparedness both physically and mentally will make the workforce difficult to compete. Drugs are one of the factors that make productive age performance not prime. The effects of addiction forced him to dwell only on quenching his thirst for taking drugs. Keywords: demographic bonus, drugs, productive, lost generation